A User Evaluation of the 2012 Fire Safety Building Regulations in Sweden and New Zealand - Wickmark,Christofer (LUTVDG/TVBB, 2014)
The purpose of this work is to evaluate and analyse the fire safety building regulations in Sweden and New Zealand that underwent significant revision in 2012. The aim of this work is to provide feedback as well as showing if the revised building regulations have achieved some of the major purposes and objectives that were the basis for the revisions. The survey method was chosen as the evaluation tool in order to provide a qualitative analysis from a user perspective. The total number of respondents that participated in the surveys were 155 in Sweden and 89 in New Zealand, out of which the majority were fire safety consultants. The results indicate that the revision of the Swedish fire safety building regulations BBR Chapter 5 was a success and that further development should follow the same path. The results further indicated that the revision of the New Zealand fire safety building regulations NZBC Clause C could not be described as a success, and that a different route may need to be considered for further work and development. Furthermore the surveys pointed to the need for additional guidance for assessment of existing as well as complex buildings in both Sweden and New Zealand.
Keywords: Building regulations; fire safety; Sweden; New Zealand; BBR; NZBC; survey